THE ROLE OF LAW IN FIELDS OF SOCIAL WORK: BETWEEN EDUCATION AND PRACTICE (AN EXPERIENCE OF GERMANY) - Vladimir P. Shalayev; Christina Niedermeier (National Research Mordova State University, 2017)
Introduction: the article deals with the development of social work as a profession and special education in Germany and the place of law in these activities. The authors analyse the impact of modern German social laws on various social groups. The place and role of law in social work fields such as poverty and unemployment between various categories of people in modern German society are given a thorough account. Materials and Methods: the authors used the historical, bibliographic, logical methods and the problematic approach. Historical and bibliographic methods are presented by the analysis of development of subject of the social work and the related social law. The logical and problem methods facilitated the understanding of the process development. Results: the influence of consequences of the World wars of the 20th c. on the German society, the social laws of the Weimar Republic, the requirement of the developed capital to education and vocational training of experts, influence of national discussions in the field of social problems, influence of international law are the main factors that have influenced the development of modern fields of social work. The Bologna Agreement plays a significant role in the educational process i n Germany. Discussion and Conclusions: the German state is the main subject of responsibility for the human condition in the society during the new challenges. The authors propose a paradigm for understanding the trend of increasing rights in society at the time of growing individualisation of a man and the destruction of traditional social institutions. These trends should be taken into account during the legal training of specialists of social services in modern Russian society with emer ging challenges of relations in a transforming society.